Contabilidade islâmica: uma análise comparativa das diferenças e semelhanças entre as normas contábeis internacionais emitidas pelo AAOIFI e IASB - El Khatib, Ahmed Sameer (2013)
Most world countries communicates with investors and stakeholders about the corporate financial performance in accordance with the International Accounting Standards issued by the International Accounting Standards Board - IASB. A group of countries, however, are not comfortable with the adoption of these standards, because understanding that they wound their principles, as is the case in Islamic countries, where religion influences the economic and financial activities of the company. Some of these countries adopt and adhere to the rules contained in the Sharia ( Islamic Law ) which brings together , in one book , a guide to social conduct, moral , ethical , religious and economic , as well as aspects of finance . Such rules have emerged with the advent of Islam in the seventh century AD and are followed to the present day, being based, including for Islamic accounting standard setters of each country and the Accounting and Auditing Organization for Islamic Financial Institution - AAOIFI, which promotes adoption of Islamic Standards of Accounting and Auditing for Islamic Financial Institutions - IFIs worldwide. Whereas research involving Islamic accounting in Brazil is still incipient and there is significant international importance , especially in relation to Islamic finance , given the volume of transactions that it focuses on an annual basis , as well as the existence of a body that issues accounting standards for IFIs , it was intended with this work to answer the following research question : What are the differences and similarities between Islamic Accounting Standards issued by AAOIFI and the International Accounting Standards issued by the IASB ? Therefore, the research involved, initially approach the characteristics and particularities of religion and Islamic finance, to then be about Islamic accounting. It has become necessary for meeting various research sources in the literature since the subject involving practically nonexistent in Brazil. We analyzed all 25 international accounting standards issued by AAOIFI by the year 2012 and the understandings of the IASB on related topics. It was concluded that there are differences in most standards, especially with regard to the Conceptual Framework, the basis for the issuance of regulations, hindering the adoption of IFRS by the Islamic Financial Institutions